Interaction of multiply charged ions with single layer graphene Part II: electron emission. (July 2015) - Fuchs-Fuchs, A; Schwestka, J; Gruber, E; Wang, Y Y; Aumayr, F
Synopsis: A new setup is used to measure the number statistics of electrons emitted during the transmission of slow multiply charged ions through single layers of graphene and 1 nm thick carbon nanomembranes.